Literasi Perpajakan dan Kualitas Pelayanan Homestay: Tax Literacy and Homestay Service Quality - Majidah, Majidah; Cahyaningsih, Cahyaningsih (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Homestay Kamojang already has several customer segments, but government agency customers require entrepreneurs to have a Taxpayer Identification Number. Likewise, homestay management still needs to have service quality standards. Therefore, community service activities through the Community Service Engagement program for homestay owner communities who join the Kamojang Homestay Association focus on homestay tax literacy and quality of homestay service. The assessment results of homestay tax literacy activities showed that most participants understood local taxes, micro, small, and medium business taxes, tax rates, and tax sanctions related to homestay tax regulations. The homestay service quality literacy assessment results showed that most participants understood the elements of service quality, criteria, and homestay functions. The majority of homestay owners have relatively good service quality elements.